Study on Profile of Benign Breast Diseases at VIMS, Pawapuri - Prasad, Bal Mukund; Lal, Prabhat Kumar; Jha, Ashok Kumar; Narayan, Rajesh (Asian Journal of Medical Research, 2019)
Background: Benign breast diseases are common cause of breast related illnesses. Proper assessment of cases is helpful in diagnosis and avoids unnecessary complications. Subjects and Methods: The present hospital based study was conducted upon 48 cases of benign breast illnesses to assess the clinico-aetiological profile. Background details of patients, detailed history and findings of clinical examination were recorded. Results: Most of the patients belonged to the age group of 21-30 years. Breast lump only was the most common presentation (62.5%), fibroadenoma was the most common cause (54.2%) and right side was most commonly involved (37.5%). Conclusion: Fibroadenoma is the most common cause of benign breast disease in this area.